2018
DOI: 10.1002/hpm.2591
|View full text |Cite
|
Sign up to set email alerts
|

The sustainability of a community nurses programme aimed at supporting active ageing in mountain areas

Abstract: Policy makers need clear information on the economic impact of extending this new intervention to the whole target population and on the required preconditions for its financial sustainability in terms of health outcomes. However, a participatory process involving all relevant local stakeholders and organisations is crucial to extend current achievements beyond project conclusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…Regarding patient-related outcomes, we found that the intervention or care delivered by FCNs significantly increased survival [ 42 , 76 , 103 ], improved quality of life and clinical outcomes [ 38 , 104 , 105 ], and reduced the re-hospitalisation rate [ 42 , 103 ]. Furthermore, Ippoliti and Falavigna demonstrated, through socioeconomic planning, how the FCN’s intervention can determine positive patient-related outcomes, such as those involving hip fractures [ 101 , 106 ]. In particular, educational intervention by FCNs allowed a better adherence to correctly measuring blood pressure to prevent cerebrovascular diseases [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding patient-related outcomes, we found that the intervention or care delivered by FCNs significantly increased survival [ 42 , 76 , 103 ], improved quality of life and clinical outcomes [ 38 , 104 , 105 ], and reduced the re-hospitalisation rate [ 42 , 103 ]. Furthermore, Ippoliti and Falavigna demonstrated, through socioeconomic planning, how the FCN’s intervention can determine positive patient-related outcomes, such as those involving hip fractures [ 101 , 106 ]. In particular, educational intervention by FCNs allowed a better adherence to correctly measuring blood pressure to prevent cerebrovascular diseases [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…Morin and colleagues developed the care management model for patients’ cardiac surgery post-intervention, following patients even after discharge from hospital in highly specialized areas [ 109 ]. In Italy, the CoNSENSo project developed model care, illuminating the necessary conditions for the continued provision of health services, and the crucial role of the FCNs to better support the daily activities of elders and their families [ 101 , 106 , 113 ]. To better understand the importance of FCNs sustaining patients and their families in the educational setting, the FN-AIM model created a map to help nursing students assess patients’ and their families’ knowledge of best practices for maintaining patient health or managing their specific conditions [ 113 , 114 ].…”
Section: Resultsmentioning
confidence: 99%
“…The current age of austerity and the related spending review policies affect national and local budgets, driving public healthcare systems to use the scarce resources available even more rationally (Ippoliti et al, ; Quaglio, Karapiperis, Woensel, Arnold, & McDaid, ; Stuckler, Reeves, Loopstra, Karanikolos, & McKee, ). The results of this research suggest that the microbiology community should consider the advantages offered by the flow cytometry technology and its additional information on urinary specimens.…”
Section: Discussionmentioning
confidence: 99%
“…The working environment is the perfect platform for the promotion of policies aimed at maintaining the psychophysical abilities of the elderly workers. In the document "Active ageing: a policy framework" the World Health Organization (WHO) defines active aging as the process of optimizing opportunities for health, participation and security in order to enhance quality of life as people age [8]. There are several evidences concerning the epidemiological, biological and clinical aspects of active aging.…”
Section: Active Aging: Definition and Lawsmentioning
confidence: 99%